Half-linear impulsive problems for classical and singular φ-Laplacian with generalized impulsive conditions - Minhós, Feliz (2019)
This paper studies separated impulsive problems with a fully third order differential equation, including an increasing homeomorphism, and impulsive conditions given by generalized functions. The arguments are based on lower and upper solutions method and a fixed point theorem.